THE INFLUENCE OF FINANCIAL DISTRESS, AUDIT OPINION, AUDIT FEE AND AUDIT DELAY ON AUDITOR SWITCHING UPGRADE, DOWNGRADE AND SAMEGRADE - Adelia Qotrunnada; Ain Hajawiyah; Budi Kurniawan (Jurnal Akuntansi, 2026)
This research aims to analyze what factors influence the change in the type of KAP upgrade. The study focuses on three types of changes in audit firm types: downgrade, upgrade, and samegrade, influenced by factors such as financial distress, audit opinion, audit fee, and audit delay. The research population consists of 92 manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022, with data obtained from their financial statements and annual reports. Using multinomial logistic regression for analysis, the results indicate that financial distress positively and significantly affects changes in samegrade audit types but does not impact changes in upgrade or downgrade types. Audit delay also shows a significant positive effect on both downgrade and samegrade audit types, while having no effect on upgrades. Conversely, the study finds that audit opinion and fee do not significantly influence any changes in audit firm types. Based on these findings, future research should consider examining sectors beyond manufacturing and include a wider array of variables, such as audit committee turnover, client size, management turnover, profitability, return on assets, and company growth.